Evaluation of the Application of APACHE II Combined With NIHSS Score in the Short-Term Prognosis of Acute Cerebral Hemorrhage Patient - Zhao, Xiao-Jing; Li, Qun-Xi; Chang, Li-Sha; Zhang, Jiang; Wang, Da-Li; Fan, Hai-Yan; Zheng, Fu-Xia; Wang, Xiu-Jie (Frontiers in Neurology, 2019)
Objective: This study aims to evaluate the recent prognosis appraised value of acute physiology and APACHE II scores in cerebral hemorrhage patients after introducing the NIHSS score. Methods: APACHE II and NIHSS scores were respectively carried out for 189 acute cerebral hemorrhage patients who were admitted to the hospital for 24 hours, and the area under ROC curve was used to measure the ability of these score systems after prognosis forecasting, in order to find the best dividing value. The discriminant analysis method should be used to carry out a comprehensive analysis to these two score methods, and establish the mathematical model to provide a reasonable basis for accurately mastering these illness conditions, and its estimation and prognosis. Results: The areas under the ROC curve of APACHE II and NIHSS scores in forecasting cerebral hemorrhage prognosis was 0.853 and 0.845, respectively, the dividing value was 15 and 17, respectively, and the forecasting accuracy was 77.2% and 79.9%, respectively; The forecasting accuracy of the combined discrimination model was 85.96%. Conclusion: APACHE II and NIHSS scores have good forecasting value to the recent prognosis of acute cerebral hemorrhage patients, and the combination of these two can provide a higher forecasting value.